Thrombophilic Evaluation in Patients with Acute Pulmonary Embolism - Stevens, Scott M.; Ansell, Jack E. (Seminars in Respiratory and Critical Care Medicine, 2017)
Patients with acute pulmonary embolism (PE) are often tested for thrombophilias, which are hereditary and acquired conditions that predispose to thrombosis. If a hereditary condition is identified, then testing is often performed on members of the patient's family. Testing for these conditions can be complex, as the presence of acute thrombosis and antithrombotic therapies can make the results of many tests unreliable. Many risk factors for thrombosis exist that are not routinely assessed by laboratory testing, and it is likely that many hereditary thrombophilia conditions remain to be discovered. Also, various risk factors for thrombosis interact with one another. Therefore, the results of a laboratory thrombophilia evaluation provide a limited ability to assess a patient or family members' risk for future thrombosis, and such testing usually does not provide information that improves a management decision. Thrombophilia testing is expensive and carries potential risks. This article reviews common thrombophilias, their epidemiology and classification, and timing and technical aspects of accurate testing and provides rational suggestions for the use of thrombophilia testing in five clinical situations: (1) following provoked PE (or other venous thromboembolism), (2) following unprovoked venous thromboembolism, (3) in relatives of patients with thrombosis, (4) in female relatives of patients with thrombosis considering estrogen use, and (5) in female relatives of patients with thrombosis who are considering pregnancy. Published guidelines and guidance statements from professional societies and other groups are also reviewed. Clinicians should carefully consider the relevant risks and benefits before testing patients for thrombophilia. When performed, testing should be timed correctly and care should be taken to properly interpret results. New models that incorporate multiple genetic and clinical markers may improve the utility of testing, but these await further research.
Keywords: thrombophilia; venous thromboembolism; deep vein thrombosis; pulmonary embolism; genetic analysis; antiphospholipid syndrome